Characterization of People Receiving 2-Drug Regimens (2DR) for HIV Management in Italy - Andrea Antinori; Spinello Antinori; Antonella Castagna; Benedetto M Celesia; Maria V Cossu; Simona Di Giambenedetto; Vincenzo Esposito; Giulia C Marchetti; Loredana Sarmati; Anna Ancona; Stefania Grieco; Stella Grattacaso; et al. (International Journal of Sexually Transmitted Diseases, 2026)
Objective To describe the clinical features and real-world treatment of people living with human immunodeficiency virus (PLHIV) using fixed-dose or free combinations of 2-drug regimens (2DR) of antiretroviral therapy (ART). Design Italian retrospective cohort study. Methods Data were extracted from PLHIV who initiated or switched to 2DR: Group 1 (fixed dose), Group 2 (free combination). Results Group 1 was younger and more predominantly male, and had shorter time from AIDS-defining diagnosis to 2DR-ART and from diagnosis to baseline, a lower prevalence of resistance, and fewer comorbidities than Group 2. Median baseline viral load was <50 copies/mL in both groups, but Group 1 had a higher mean due to outliers. The most common ART classes before switching to 2DR were Integrase Strand Transfer Inhibitor (INSTI)-based (48.97%), Non-Nucleoside Reverse Transcriptase Inhibitor (NNRTI)-based (22.73%), and Protease Inhibitor (PI)-based (16.53%). Distribution varied: Group 1: INSTI-based (53.13%), NNRTI-based (24.31%), and PI-based (15.04%); Group 2: INSTI-based (29.41%), PI-based (23.53%), and NNRTI-based (15.29%). After switching, Group 1 was on dolutegravir/lamivudine (79,33%) and dolutegravir/rilpivirine (20,67%); Group 2 mostly on INSTI-PI (52.81%), followed by NNRTI combinations, mainly with doravirine (19.10%). Duration of ART after switching was shorter in Group 1. Conclusion Italian PLHIV on 2DR fixed-dose combinations were younger, virologically suppressed individuals at baseline, with a shorter lead time from diagnosis, lower prevalence of resistance and lower comorbidity rate compared to those on free combinations. These findings underscore an unmet need for 2DR fixed-dose combinations, as the free combinations were predominantly utilized for more challenging populations.
Keywords: 2-drug regimens